Analisis Implementasi Pernyataan Standar Akuntansi Keuangan 109 - Abdul Hakim Siregar; Ikhwanuddin Harahap; Delima Sari Lubis (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
AbstractCash receipts from zakat and infaq funds will increase zakat and infaq / alms funds, and the distribution of zakat funds will reduce the cash of zakat and infaq funds, which is called the double entry recording system, while the recording carried out by BAZNAS Tapanuli Selatan only applies the method single entry, the recording system is indeed simple and easy to understand, but it cannot produce complete financial reports, it is difficult to find errors that occur and difficult to control. BAZNAS Tapanuli Selatan has not fully implemented PSAK 109 in South Tapanuli BAZNAS. BAZNAS Tapanuli Selatan has implemented part of PSAK 109 in the financial statements and the information required in PSAK 109 in BAZNAS's financial statements can be found but there are still a series of BAZNAS financial reports that have not been owned based on the PSAK reference, namely Cash Flow Statements and Notes to Financial Statements. Keyword : Zakah, PSAK 109, BAZNAS